Opimalisasi Peningkatan Penjualan Melalui Pendampingan Pemasaran Digital Marketing Bagi Pelaku UMKM Binaan Puspa Binjai - Neni Sri Wahyuni; T Ahmad Helmi; Muhammad Nelson Pinem; Supar Wasesa; Sri Rahayu; Sugi Hartati; Fikri Al-Haq Fachryana; Deddy Pranata (JPM: Jurnal Pengabdian Masyarakat, 2022)
Technological developments are unavoidable nowadays. Almost all organizations or levels of society have accepted technological developments. The business sector is one of the sectors that has a significant influence on the development of this technology. Where with the existence of the internet, the habitual patterns of buyers have left conventional methods, namely direct face-to-face meetings between sellers and buyers to become digital / online. By using the online method, the buyer does not need to visit or meet with the seller, the whole process can be done online using available online shopping sites. Digital marketing is one of the business strategies that can be applied in carrying out business processes for organizations or business people. The use of digital marketing is not only used by large organizations, but can also be used by SMEs. This research was conducted on FK PUSPA's assisted SMEs, which totaled approximately 35 SMEs. The result of the service activity is to market the products of SMEs actors by optimizing digital marketing so that income increases. This activity provides benefits for participants, namely SMEs practitioners in obtaining maximum knowledge/insight on product sales activities and can increase income.